Illness as Metaphor? The Role of Linguistic Categories in the History of Medicine - Ulrike Kistner (Studies in 20th & 21st Century Literature, 1998)
Susan Soniag's studies on "Illness and Metaphor" raise a host of questions, based on the twin suppositions running through her project: the ubiquity and pervasiveness of metaphoric constructions of illness on the one hand, and the vision of a liberation from metaphors of illness on the other hand. This paper sets itself the task to explain and resolve this paradox. To this end, concepts of metaphor have to be linguistically defined and differentiated, both structurally and within an archaeology of (medical) knowledge; for it is only on the basis of such a differentiation that we can show how metaphorical language can operate both in a "pre-scientific" or (modern) mythical function, and in scientific statements, where the demonstration of causality is at issue. However, this investigation is not confined to linguistics and logic; it is moreover shown in its relevance for the history of medicine, insofar as modern medicine is still grappling with logical problems of causality in diagnosis and treatment, calling forth different kinds of metaphoric constructions with different types of assertive or explanatory power.
Keywords: Susan Soniag; Illness and Metaphor; ubiquity; pervasiveness; metaphoric constructions of illness; illness; metaphor; liberation; paradox; medical knowledge; metaphorical language; pre-scientific; modern; myth; linguistics; logic; modern medicine